If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -9x = 41 + -16x Solving 7 + -9x = 41 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. 7 + -9x + 16x = 41 + -16x + 16x Combine like terms: -9x + 16x = 7x 7 + 7x = 41 + -16x + 16x Combine like terms: -16x + 16x = 0 7 + 7x = 41 + 0 7 + 7x = 41 Add '-7' to each side of the equation. 7 + -7 + 7x = 41 + -7 Combine like terms: 7 + -7 = 0 0 + 7x = 41 + -7 7x = 41 + -7 Combine like terms: 41 + -7 = 34 7x = 34 Divide each side by '7'. x = 4.857142857 Simplifying x = 4.857142857
| 108=2(6+2w)+2(x) | | 9*(7-4)2+9= | | 230-6x=39x+15 | | 159-2x=25x+15 | | 2-3=11 | | 3(3x-2)+17=7x+3 | | -31x-2x=5-8x | | 13x^2+5x-8=0 | | 5xy+7=62 | | X^2+5x=x^2-x-12 | | 6x-5=4x+15 | | 9x+10(2x+33000)=45640 | | -4-11=4r+21 | | -9=t-11 | | 2x+8=64-5 | | 12-9x=157-44x | | 2-ax=-8 | | x^3+3x=85 | | .333(x-2)=4 | | 5x+10(3x+44000)=513000 | | 7xy+2yx+8xy= | | 3x-8(4x-6)+8(x+4)=0 | | X-4x=-25+3+22 | | s-14.2=-18.7 | | 5(x-3)-2(x+1)=4 | | (5x^2+7x)(12x^2-5x-3)=0 | | 3x+15=74-3x | | -9x+23=88 | | -24+18= | | p+(-26)=-13.8 | | (x^2-xy+y^2)+3xy=0 | | 2f-3g+5g-6f= |